SARS-CoV-2 Is Not Detected in the Cerebrospinal Fluid of Encephalopathic COVID-19 Patients - Placantonakis, Dimitris G.; Aguero-Rosenfeld, Maria; Flaifel, Abdallah; Colavito, John; Inglima, Kenneth; Zagzag, David; Snuderl, Matija; Louie, Eddie; Frontera, Jennifer Ann; Lewis, Ariane (Frontiers in Neurology, 2020)
Neurologic manifestations of the novel coronavirus SARS-CoV-2 infection have received wide attention, but the mechanisms remain uncertain. Here, we describe computational data from public domain RNA-seq datasets and cerebrospinal fluid data from adult patients with severe COVID-19 pneumonia that suggest that SARS-CoV-2 infection of the central nervous system is unlikely. We found that the mRNAs encoding the ACE2 receptor and the TMPRSS2 transmembrane serine protease, both of which are required for viral entry into host cells, are minimally expressed in the major cell types of the brain. In addition, CSF samples from 13 adult encephalopathic COVID-19 patients diagnosed with the viral infection via nasopharyngeal swab RT-PCR did not show evidence for the virus. This particular finding is robust for two reasons. First, the RT-PCR diagnostic was validated for CSF studies using stringent criteria; and second, 61% of these patients had CSF testing within 1 week of a positive nasopharyngeal diagnostic test. We propose that neurologic sequelae of COVID-19 are not due to SARS-CoV-2 meningoencephalitis and that other etiologies are more likely mechanisms.